Optimalisasi Pengendalian Persediaan Bahan Baku untuk Meminimalkan Biaya Persediaan Menggunakan Metode Economic Order Quantity (EOQ) di PT XYZ - Widyantika, Wandah; Purnama, Jaka (Fakultas Teknik UMRI, 2026)
Delays and shortages of raw materials in the plastic bag production process can disrupt production activities and increase the company’s operational costs. This study aims to analyze the application of the Material Requirements Planning (MRP) method in raw material planning to ensure that material availability is fulfilled in the right quantity and at the right time. The research process begins with demand forecasting, followed by the application of the Economic Order Quantity (EOQ) method to determine the optimal raw material order quantity in order to control inventory costs efficiently. In addition, an analysis of operational losses caused by one hour of production idle time was conducted using a loss profit approach based on income and company expenses. The results show that the implementation of the EOQ method generated total inventory costs of Rp216,740,485, indicating that the method is effective for application in PT XYZ. The idle time analysis revealed total labor losses of Rp256,200.87, consisting of income losses of Rp239,488.61 and company expenses of Rp16,712.26. These findings indicate that delays in raw material supply not only hinder the production process but also lead to operational losses because the company must continue to incur labor costs during production idle time.